2012
DOI: 10.1159/000339207
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Mitochondrial DNA Damage in Blood and Brain Tissues of a Transgenic Mouse Model of Machado-Joseph Disease

Abstract: Background: Machado-Joseph disease (MJD) is an autosomal dominant spinocerebellar ataxia caused by a CAG tract expansions in the ATXN3 gene. Patterns of mitochondrial damage associated with pathological findings of brain tissues could provide molecular biomarkers of this disorder. Objective: The potential of mitochondrial DNA (mtDNA) damage as a biomarker of MJD progression was investigated using a transgenic mouse model. Methods: DNA was obtained from affected (pontine nuclei) and nonaffected tissues (hippoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 19 publications
(30 reference statements)
6
41
0
Order By: Relevance
“…In accordance with this, a cell model overexpressing mutant ataxin-3 with 78 CAGs showed reduced antioxidant enzyme levels, increased mitochondrial DNA damage, and reduced energy supply, which indicates impaired mitochondrial function [124]. Recently, mitochondrial DNA damage was also seen in SCA3 transgenic mice expressing full-length ataxin-3 with 98 to 104 glutamines [125]. In the disease-affected pontine nuclei of these transgenic SCA3 mice, less mitochondrial DNA copies were seen, as compared to the unaffected hippocampus [125].…”
Section: Mitochondrial Dysfunction In Sca3mentioning
confidence: 88%
See 1 more Smart Citation
“…In accordance with this, a cell model overexpressing mutant ataxin-3 with 78 CAGs showed reduced antioxidant enzyme levels, increased mitochondrial DNA damage, and reduced energy supply, which indicates impaired mitochondrial function [124]. Recently, mitochondrial DNA damage was also seen in SCA3 transgenic mice expressing full-length ataxin-3 with 98 to 104 glutamines [125]. In the disease-affected pontine nuclei of these transgenic SCA3 mice, less mitochondrial DNA copies were seen, as compared to the unaffected hippocampus [125].…”
Section: Mitochondrial Dysfunction In Sca3mentioning
confidence: 88%
“…Recently, mitochondrial DNA damage was also seen in SCA3 transgenic mice expressing full-length ataxin-3 with 98 to 104 glutamines [125]. In the disease-affected pontine nuclei of these transgenic SCA3 mice, less mitochondrial DNA copies were seen, as compared to the unaffected hippocampus [125]. Additionally, less mitochondrial DNA copy numbers were observed in the mutant cells and SCA3 patient samples, implying mitochondrial DNA damage due to oxidative stress [124].…”
Section: Mitochondrial Dysfunction In Sca3mentioning
confidence: 99%
“…Oxidative stress is associated with the pathogenesis of SCA3 disease (40,41). Previously, it was demonstrated that CSE deficiency is linked to increased levels of oxidative stress (42).…”
Section: Overexpression Of Cse Reduces Levels Of Oxidative Damage Of mentioning
confidence: 99%
“…In humans, defects in mtDNA maintenance generated by mutations in genes involved in mtDNA replication and nucleotide biosynthesis cause mtDNA depletion syndromes (MDS) (El-Hattab and Scaglia, 2013). Such mtDNA depletions are also associated with metabolic diseases, including type 2 diabetes, cancers and neurodegenerative disorders, including Alzheimer’s, Parkinson’s and Machado-Joseph disease (Abolhassani et al, 2016; Kazachkova et al, 2013; Ramos et al, 2015; Sepe et al, 2016). During aging, mtDNA copy number also decreases, probably because it is prone to oxidative damage by reactive oxygen species (ROS) produced in the mitochondrial matrix.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, several reports have shown that aging leads to mtDNA damage and dysfunction (Bratic and Larsson, 2013; Gomez-Cabrera et al, 2012; Kennedy et al, 2012; Trifunovic and Larsson, 2008). In such cases, quantification of the mtDNA damage and analysis and quantification of the mtDNA copy number may be a good biomarker for disease progression and development of therapies (Kazachkova et al, 2013). In non-pathological or aging-related conditions, mtDNA quantification is also a good indicator of the mitochondrial mass.…”
Section: Introductionmentioning
confidence: 99%